Spatiotemporal Phylodynamics of Hepatitis C Among People Who Inject Drugs in India. Issue 4 (25th August 2021) - Clipman, Steven J.; Mehta, Shruti H.; Rodgers, Mary A.; Duggal, Priya; Srikrishnan, Aylur K.; Saravanan, Shanmugam; Balakrishnan, Pachamuthu; Vasudevan, Canjeevaran K.; Ray, Stuart C.; Kumar, Muniratnam S.; Quinn, Thomas C.; Cloherty, Gavin A.; et al.
Abstract : Background and Aims: Implementing effective interventions for HCV requires a detailed understanding of local transmission dynamics and geospatial spread. Little is known about HCV phylodynamics, particularly among high‐burden populations, such as people who inject drugs (PWID). Approach and Results: We used 483 HCV sequences and detailed individual‐level data from PWID across four Indian cities. Bayesian phylogeographic analyses were used to evaluate transmission hotspots and geospatial diffusion of the virus. Phylogenetic cluster analysis was performed to infer epidemiologic links and factors associated with clustering. A total of 492 HIV sequences were used to draw comparisons within the same population and, in the case of coinfections, evaluate molecular evidence for shared transmission pathways. Overall, 139/483 (28.8%) of HCV sequences clustered with a median cluster size of 3 individuals. Genetically linked participants with HCV were significantly younger and more likely to be infected with HCV subtype 3b as well as to live and inject close to one another. Phylogenetic evidence suggests likely ongoing HCV infection/reinfection with limited support for shared HIV/HCV transmission pathways. Phylogeographic analyses trace historic HCV spread back to Northeastern India and show diffusion patterns consistent with drug trafficking routes. Conclusions: This study characterizes HCV phylodynamics among PWID in a low and middle‐income country setting. Heterogeneity and recent genetic linkage of HCV across geographically disparate Indian states suggest that targeted interventions could help prevent reimportation of virus through drug trafficking routes.